Effect of incorporation of dietary fibers on reduced calorie Kulfi containing whey protein concentrate - Giri, Apurba (Indian Journal of Dairy Science, 2025)
To improve the dietary value of Kulfi, 50% of the sugar was replaced by stevia (at 0.05%), 3% whey protein concentrate (WPC) was added along with - 0.5 and 1% dietary fiber [pectin and wheat bran (WB)]. As the level of pectin and WB addition increased the specific gravity increased and freezing point decreased. At 1% pectin and WB addition the melting rate decreased and at 1% pectin and 0.5 and 1% WB addition there was a significant increase in hardness. Based on sensory analysis Kulfi with 0.5% added pectin was judged to be on a par with the control.